MAINTAINING BAHASA ACEH IN KEUDE KUPI AMONG TEENAGERS IN MEDAN - Emalia Amna; Anni Holila Pulungan; Rahmad Husein (LINGUISTIK TERAPAN, 2018)
This study focuses specifically on investigating the maintenance of Bahasa Aceh by Acehnese teenagers in keude kupi in Medan. It employs qualitative research method and applies a case study design. The subjects were ten Acehnese Teenagers in keude kupi in Medan. The instruments used for this study were observation, interview and document gathering. The observation was applied to get the data about the language they used in the keude kupi. The interview was applied to get the data for answering the three questions of this study; factors affecting Bahasa Aceh maintenance, the manners done by the teenagers and the reasons for maintaining the language in keude kupi. While the documentation needed to give a visual data about the subjects and site of the study. The data were analysed by using Ethnography Method, proposed by Spradley. It has been found that there were some factors lead to the maintenance of Bahasa Aceh, they are: language attitude, parents’ role, environment, visiting homeland continuously and intra-marriage. The maintenance of Bahasa Aceh was done by keep using it to other Acehnese, read the Acehnese online or printed media, and watch or listen to the Acehnese entertainment. In maintaining their mother language, the teenagers’ reasons were not only about showing their identity, help their community to progress and achieving self-esteem and/or self-pride, but also to create the feel-like-home situation, since using the language with the same Acehnese peers makes them feel closer and bound.Keywords: Language Maintenance, Bahasa Aceh, Teenagers, Keude Kupi